Antioxidant mechanisms of mesenchymal stem cells and their therapeutic potential in vitiligo - Yang, Rui-lin; Chen, Si-yu; Fu, Sheng-ping; Zhao, De-zhi; Wan, Wei-hong; Yang, Kang; Lei, Wei; Yang, Ying; Zhang, Qian; Zhang, Tao (Frontiers in Cell and Developmental Biology, 2023)
Vitiligo is a skin pigmentation disorder caused by melanocyte damage or abnormal function. Reactive oxygen species (ROS) can cause oxidative stress damage to melanocytes, which in turn induces vitiligo. Traditional treatments such as phototherapy, drugs, and other methods of treatment are long and result in frequent recurrences. Currently, mesenchymal stem cells (MSCs) are widely used in the research of various disease treatments due to their excellent paracrine effects, making them a promising immunoregulatory and tissue repair strategy. Furthermore, an increasing body of evidence suggests that utilizing the paracrine functions of MSCs can downregulate oxidative stress in the testes, liver, kidneys, and other affected organs in animal models of certain diseases. Additionally, MSCs can help create a microenvironment that promotes tissue repair and regeneration in areas with oxidative stress damage, improving the disordered state of the injured site. In this article, we review the pathogenesis of oxidative stress in vitiligo and promising strategies for its treatment.